Medical Students’ Tobacco Consumption Status and Experiences with Smoke-free Law Violations in Enclosed Spaces in Türkiye and Northern Cyprus - Dilek Aslan; Pınar Ay; Kervin Raymond; Özen Aşut; Gulifeiya Abuduxike; Meltem Şengelen; Duygu Çekici; Füsun Yıldız; Emine Ünal Evren; Ali Fuat Kalyoncu; Elif Dağlı (Thoracic Research and Practice)
OBJECTIVE: This study aimed to determine the frequency of tobacco smoking among medical students and assess their exposure to violations of smoke-free laws in enclosed spaces 30 days before the study. It also identifies key locations where such infractions occur and explores associated factors. MATERIAL AND METHODS: A descriptive study was conducted using a questionnaire-based survey among students from two public and two private medical faculties in Türkiye and Northern Cyprus in 2023. Of the invited students, 628 responded. Data were analyzed using IBM Statistical Package for the Social Sciences statistics for Windows, version 23.0. Descriptive statistics included frequencies, percentages, means±standard deviations, and medians (interquartile ranges). Relationships between categorical variables were assessed using chi-squared and Fisher’s exact tests, with significance set at P < 0.05. Binary logistic regression analysis of predictors of exposure to smoke-free violations was conducted. Ethical approval was obtained from each university. RESULTS: Most participants were female (56.4%), with a mean age of 21.5±2.37 years. Nearly one in five students was a current tobacco user (19.9%). Smokers had higher exposure to passive smoking than non-smokers (92.0% vs. 82.5%, P = 0.009). Encountering tobacco industry-branded vehicles was associated with higher exposure (92.3% vs. 83.7%, P = 0.03). Exposure to violations of the antismoking ban in enclosed spaces was significantly higher among students who smoked with higher frequency (odds ratio: 2.418, 95% confidence interval: 1.172 to 4.990, P = 0.017). CONCLUSION: This study underscores the need for strict tobacco control among medical students, with an emphasis on advocacy and interdisciplinary collaboration to combat the tobacco industry’s influence.